"The Time of Lament": A Momand drama of 1711 through the eyes of Pashtun litterateurs. (3rd February 2021) - Pelevin, Mikhail
Abstract: This article offers a comparative examination of the literary responses of four leading early modern Pashtun authors to an armed clash in the Momand tribe in 1711. The responses include a chronicle record in prose (Afżal Khān Khaṫak) and three poems – an elegy (ʿAbd al-Raḥmān Momand), a satire (ʿAbd al-Ḥamīd Momand), and a war ode (ʿAbd al-Qādir Khaṫak). Discussed as both authentic historical documents and creative writings linked to a local social discourse, these Pashto texts enable us to reassess the intensity of everyday literary communications in Pashtun tribal areas in early modern times and append new factual material to the study of ethno-cultural processes within the Persophone oecumene. The salient stylistic and rhetoric diversity of the texts not only highlights the authors' individual mindsets and literary techniques, but also provides an insight into a variety of social moods, political attitudes and ethics in the Pashtun traditional society.